2022
DOI: 10.3389/fcvm.2022.851833
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Outcomes in the Patients With Colorectal Cancer: A Multi-Registry-Based Cohort Study of 197,699 Cases in the Real World

Abstract: PurposeWe aimed to investigate the mortality patterns and quantitatively assess the risks of cardiovascular death (CVD) in patients with colorectal cancer (CRC). We also established a competing-risk model to predict the probability of CVD for patients with CRC.Patients and MethodsPatients with CRC who diagnosed between 2007 and 2015 in the Surveillance, Epidemiology, and End Results (SEER) database were included in the present study. The cumulative incidence function (CIF) was used for CVD and other causes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…In recent years, socioeconomic factors, including cultural and social values, insurance status, educational level, and employment status, have increasingly become a focus of attention in the medical eld [45] . We observed that marital status is a risk factor for both cancer-speci c mortality (CSM) and overall survival (OCM).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, socioeconomic factors, including cultural and social values, insurance status, educational level, and employment status, have increasingly become a focus of attention in the medical eld [45] . We observed that marital status is a risk factor for both cancer-speci c mortality (CSM) and overall survival (OCM).…”
Section: Discussionmentioning
confidence: 99%
“…Harrell’s concordance C-index was calculated using bootstrap resampling (1000 replications) to measure the discriminatory ability of the nomograph. Consistency was gauged by calibration curves, while the predictive effect of the model was verified using the ROC curve and AUC[ 5 , 24 ]. In addition, the net clinical benefit of the nomograph was estimated via decision curve analysis (DCA).…”
Section: Methodsmentioning
confidence: 99%
“…In the last decade, CVD has been recognized as one of the most frequent advanced comorbidities of cancer treatment[ 5 ]. Advances in therapeutic approaches, especially the advent of immunotherapies, have revolutionized cancer treatment, allowing the lifespan of cancer patients to be extended, but at the same time leading to millions of cancer survivors currently at risk of developing CVD[ 6 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This was higher with higher intensity treatment (six cycles) [18]. CVD was also observed in those treated for colorectal cancer, with 1-, 3- and 5-year cumulative rates for CVD being 12.20%, 24.25% and 30.51%, respectively [19]. The prevalence of ischaemic stroke was three-times higher in those treated for nasopharyngeal cancer than those in a comparative non-cancer population [15].…”
Section: Physical Late Effects Of Cancer Treatmentmentioning
confidence: 99%
“…Risk was highest in the first year after diagnosis (HR = 7.47, 95% CI 6.66–8.37) and reduced overtime. Still an increased risk at 5 years post treatment Association between AKI and colorectal cancer treatment was greater for younger patients, men and those with pre-existing chronic kidney disease Zhang et al 2022 [19]Sweden Retrospective registry study of 197 699 people diagnosed with colorectal cancer between 2007 and 2015. Study explored the mortality patterns and risks of cardiovascular disease events No comparative normative data Median follow-up of 37 months 79 455 deaths occurred of which 29.29% died through non-cancer events which CVD made up 41.69% The 1, 3 and 5-year cumulative rate for CVD was 12.20%, 24.25% and 30.51%, respectively Age, race, marital status, tumour size, stage, surgery, and chemotherapy were independent risk factors of CVD Chen et al 2019 [15]Taiwan Retrospective cohort study of 3016 people diagnosed with nasopharyngeal cancer between 2005 and 2012.…”
Section: Introductionmentioning
confidence: 99%